Hesitancy of Influenza Vaccination in Thai Patients with Type 2 Diabetes Mellitus: A Cross-sectional Study in Burapha University Hospital, Chonburi, Thailand - Thammakumpee, Katkanit; Sapsirisavat, Vorapot (Asian Medical Journal and Alternative Medicine, 2021)
Objective: Despite influenza vaccines being recommended to patients with type 2 diabetes (T2DM), the coverage was still low. This study measured influenza vaccine hesitancy and identify associated factors among T2DM patients at the Burapha University Hospital. Methods: This cross-sectional study was conducted during May-August 2020. Participants were recruited from T2DM patients visited the hospital for continuity care. The research gathered demographic data; medical data were retrieved from electronic medical records. Statistical analysis was performed for those who received the influenza vaccine compared to those who decided not to receive the vaccine. Results: A total of 304 T2DM patients (female 54%, mean age 63 years, BMI 26.49kg/m2, HbA1c 7.63%) were included into the study. One-third (30.6%) never had the vaccine. The hesitancy rate was 38%. When adjusted for demographic and medical data, T2DM patients aged< 65 years and never had influenza vaccines were significantly associated with the hesitancy.The top reason overall was lack of knowledge and awareness. Many patients did not haveinfluenza vaccination because they had never received a vaccine recommendation from a primary provider. Conclusions: Hesitancy to influenza vaccination was substantial among our T2DM patients especially those who were younger and never had the vaccine. Primary providers have a major role to raise the knowledge and awareness of influenza vaccine toward this vulnerable population. This article has a correction. Please see: Erratum for the Research Article “Hesitancy of Influenza Vaccination in Thai Patients with Type 2 Diabetes Mellitus: A Cross-sectional Study in Burapha University Hospital, Chonburi, Thailand” by Katkanit Thammakumpee and Vorapot Sapsirisavat 29 September 2022